THE EFFECT OF ANTICOAGULANT TYPES ON THE IN VITRO ANALYSIS OF CLOPIDOGREL IN HUMAN PLASMA USING LIQUID CHROMATOGRAPHY TANDEM-MASS SPECTROMETRY - Harahap, Yahdiana; Maulidina, Anisa; Ramadon, Delly (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to optimize and validate a plasma clopidogrel analysis method using liquid chromatography tandem-mass spectrometry. Methods: Plasma samples were analyzed using a BEH C18 column (1.7 Î¼m; 100 mmÃ—2.1 mm), the mobile phase was 0.1% formic acid in acetonitrile (30:70, v/v). The flow rate was 0.2 mL/min, with a column temperature set to 35Â°C, an injection volume of 5 Î¼L, an analysis time of 4 min, and irbesartan as the internal standard. Aliquots were obtained by liquid-liquid extraction using ammonium acetate and diethyl ether. The stability and peak area ratio of the respective plasma area responses were evaluated using ANOVA. Results: No significant differences (p>0.05) were observed between anticoagulants regarding analyte stability. However, the peak area ratio showed significant differences (p<0.05) between the anticoagulants. The accuracy and precision of the analysis with citrate, heparin, and ethylenediaminetetraacetic acid (EDTA) plasma met the quality requirements, and a linear calibration curve was created with concentrations ranging from 0.02 to 5.0 ng/mL. Conclusion: The results showed that improved analysis of clopidogrel was achieved using citrate or heparin plasma compared with EDTA plasma.